Pathogenesis of acute hepatopancreatic necrosis disease caused by vibrio spp. in whiteleg shrimp Penaeus vannamei (Boone, 1931) - Muthukrishnan, Sarmila (2020)
Acute hepatopancreatic necrosis disease (AHPND) first emerged as a new shrimp disease in 2009 and has heavily affected the shrimp industry leading to global economic losses. The aetiological agent was previously identified as Vibrio parahaemolyticus that carries a pVA1-type plasmid carrying pirABvp toxins. However, previous research revealed that V. parahaemolyticus is not the only bacterial species capable of causing AHPND. Hence, the objectives of this study is (1) to isolate, screen, characterise, and identify the AHPND positive bacteria from the whiteleg shrimp Penaeus vannamei in Malaysia, (2) to screen and elucidate the involvement of quorum sensing (QS) in AHPND positive bacteria in in vitro and (3) in vivo and finally, (4) to assess the horizontal gene transfer of AHPND causing genes from AHPND positive bacterium to a non-AHPND causing bacterium. Sampling of whiteleg shrimp was carried out at iSharp, Terengganu shrimp farm, which located at the east coast of Peninsular Malaysia, to isolate the AHPND causing bacteria. Preliminary pathogenicity study was conducted using brine shrimp, Artemia franciscana as a model organism. The most pathogenic bacteria from the brine shrimp challenge test was employed in the whiteleg shrimp challenge test. Histopathology analysis was performed to further study the clinical signs and AHPND’s pathology. The AHPND positive isolates were identified using multilocus sequencing analysis (MLSA) and biochemical tests. Three types of quorum sensing (QS) signal molecules, namely, N-acyl-homoserine lactone (AHL), Autoinducer-2 (AI-2), and Cholerae autoinducer-1-like (CAI-1) molecules were then screened in the AHPND positive isolates using Agrobacterium tumefaciens KYC55, Vibrio campbellii JMH597, and V. campbellii JAF375 biosensors respectively. Molecular screening of the QS-related genes, luxR and luxS was conducted to justify the in vitro activity of QS in AHPND positive isolates. The in vivo gene expression study of pirA, pirB, toxR, and luxR genes in whiteleg shrimp using quantitative PCR (qPCR) was conducted to study the expression patterns during the infection. A superoxide dismutase (SOD) was performed to study the oxidative state during the infection. Finally, a horizontal gene transfer (HGT) study was demonstrated by co-culturing the AHPND positive bacteria and the non-AHPND bacteria to evaluate the conjugation efficiency rate (n°). Out of the 86 isolates, 12 isolates were screened positive for AHPND using conventional polymerase chain reaction (PCR) method. All the 12 AHPND positive isolates with pirA and pirB genes demonstrated significant (P < 0.05) mortalities (23-97%) of brine shrimp compared to the negative control (2%). Based on 16S rRNA, RctB, and RpoD sequencing analysis, the 12 isolates belong to the Harveyi clade and identified as V. parahaemolyticus (7 isolates) and Vibrio harveyi (5 isolates). Further test showed that the yellow colony V. harveyi BpShHep24 (100% mortalities in 48 h) was found to be more virulent than the green colony V. parahaemolyticus BpShHep31 (50% mortalities in 48 h) in the whiteleg shrimp challenge test. The histopathology analysis of the challenged shrimp demonstrated terminal stage characteristics of AHPND pathology. All the three types of QS signal molecules were detected in AHPND positive V. parahaemolyticus and V. harveyi. The luxR and luxS gene screening was positive for all the 12 AHPND positive isolates. The formation of biofilm increased with the increase in AHL concentration (1-100 nmol L-1 ) in 11 AHPND positive isolates and demonstrated that the QS signal molecules control the formation of biofilm in AHPND positive Vibrio isolates. The expression of AHPND virulence factors, quorum sensing regulator luxR, and virulence regulator toxR in whiteleg shrimp challenged with V. parahaemolyticus BpShHep31 and V. harveyi BpShHep24 demonstrated a significant (P < 0.05) increase of the quorum sensing master regulator luxR when compared with the control shrimp (unchallenged group). There was also a substantial difference in pirA, pirB, and toxR expressions in the challenged shrimp compared to the unchallenged shrimp. However, shrimp challenged with V. harveyi BpShHep24 demonstrated 8.7-, 17.4-, 13.3-, and 21.8- fold higher expression of pirA, pirB, toxR, and luxR respectively when compared to shrimp challenged with V. parahaemolyticus BpShHep31. The superoxide dismutase (SOD) study in the challenged shrimp has shown an expression peak of oxidative stress at 24 h post challenged and followed by a reduced expression level. Furthermore, the protein content in the challenged group decreases, suggesting poor growth performance due to the stress induced by the pathogens. In general, the in vivo gene expression study, SOD study, and protein content analyses demonstrated a clear difference between the challenged (with AHPND positive isolates) and unchallenged shrimp. The present study also demonstrated occurrence of HGT from AHPND positive V. parahaemolyticus to a non-AHPND and non-Vibrio species identified as Algoriphagus sp. strain NBP. The HGT of pirA and pirB genes from the AHPND positive V. parahaemolyticus to Algoriphagus sp. strain NBP was found to occur at three different temperatures (20°C, 30°C, and 40°C). The conjugation efficiency rate (n°) of pirAB from V. parahaemolyticus to Algoriphagus sp. strain NBP at 30°C and 40°C showed 80% to 91% efficiency. Shrimp challenged with the pirA and pirB positive Algoriphagus sp. strain NBP also demonstrated typical pathognomonic AHPND lesions during the histopathologic examination. In conclusion, this study documented the types of Vibrio spp. involved in AHPND outbreak in Malaysia. All the 12 AHPND positive isolates were positive for QS screening and positively correlates with AHPND virulence genes (pirA and pirB). Virulence factors produced by the pathogen play a vital role in spreading the infection in aquaculture farms. Therefore, the foremost aspect is to understand the virulence mechanisms involved during the infection which may aid in developing proper mitigation and sustainable method to control the disease outbreak in aquaculture farms.